Electrochemical study of reactions at interfaces of glucose oxidase collagen membranes - Coulet, P.R.; Sternberg, R.; Thevenot, D.R. (Biochimica et biophysica acta, 1980)
The operational behaviour of enzyme collagen membranes with surface-bound glucose oxidase has been studied by simultaneously recording the current outputs of two platinum anodes: whereas the first one was close to the enzymatic membrane, the second was placed into the bulk solution. Steady-state responses of both electrodes were measured when either glucose or hydrogen peroxide were added to the stirred buffer solution. They were used to determine the hydrogen peroxide fluxes, v1 (toward the first electrode) and v2 (towards the bulk phase). The glucose concentration and temperature dependence of v1 and v2 have been studied and the importance of diffusional limitations on the overall reaction rates were determined. Comparison of freely stirred and mounted enzymatic membrane enabled us to determine an equivalent working area at high glucose concentration.